Cancer susceptibility syndromes in children in the area of broad clinical use of massive parallel sequencing - Kuhlen, Michaela (Eur J Pediatr, 2015)
Children diagnosed with cancer are considered for inherited cancer susceptibility testing according to well-established clinical criteria. With increasing efforts to personalize cancer medicine, comprehensive genome analyses will find its way into daily clinical routine in pediatric oncology. Whole genome and exome sequencing unavoidably generates incidental findings. The somatic “molecular make-up” of a tumor genome may suggest a germline mutation in a cancer susceptibility syndrome. At least two mechanisms are well-known, (a) chromothripsis (Li-Fraumeni syndrome) and (b) a high total number of mutational events which exceeds that of other samples of the same tumor type (defective DNA mismatch repair). Hence, pediatricians are faced with the fact that genetic events within the tumor genome itself can point toward underlying germline cancer susceptibility. Whenever genetic testing including next-generation sequencing (NGS) is initiated, the pediatrician has to inform about the benefits, risks, and alternatives, discuss the possibility of incidental findings and its disclosure, and to obtain informed consent prior to testing. Conclusions: Genetic testing and translational research in pediatric oncology can incidentally uncover an underlying cancer susceptibility syndrome with implications for the entire family. Pediatricians should therefore increase their awareness of chances and risks that accompany the increasingly wide clinical implementation of NGS platforms.